Identification of Novel, Immunogenic HLA–DR‐Presented Prevotella copri Peptides in Patients With Rheumatoid Arthritis. Issue 12 (22nd October 2021) - Pianta, Annalisa; Chiumento, Geena; Ramsden, Kristina; Wang, Qi; Strle, Klemen; Arvikar, Sheila; Costello, Catherine E.; Steere, Allen C.
Abstract : Objective: We previously identified HLA–DR‐presented epitopes from a 27‐kd protein of Prevotella copri (Pc) obtained from peripheral blood mononuclear cells (PBMCs) from 1 rheumatoid arthritis (RA) patient. Herein, we sought to identify other HLA–DR‐presented Pc peptides and source proteins in PBMCs from additional patients to better understand Pc immune responses and RA disease pathogenesis. Methods: Using tandem mass spectrometry, we searched for HLA–DR‐presented Pc peptides in PBMCs from RA and Lyme arthritis (LA) patients. The identified peptides and source proteins were tested for reactivity in RA patients, those with other arthritides, and the general population. These results were assessed for correlation with clinical findings. Results: Including Pc‐p27, we identified 5 HLA–DR‐presented Pc peptides, each derived from a different Pc protein, in 3 of 4 RA patients, but none in 2 LA patients. When tested in our RA cohort, 14 of 19 patients (74%) had T cell responses, and 47 of 89 patients (53%) had IgG or IgA responses to ≥1 of the 5 Pc peptides or proteins, most commonly IgA reactivity with Pc‐p27. Additionally, 74% of RA patients with IgA antibodies to ≥1 Pc protein had anti–citrullinated protein antibodies (ACPAs) compared with 49% of patients who lacked IgA Pc antibody responses ( P = 0.05), and IgA Pc antibody levels correlated with ACPA values. Conclusion: The majority of the RA patients had Pc immune responses. The correlation of IgA Pc antibody responses, particularly to Pc‐p27, with ACPA supports the hypothesis that specific microbial antigens in the mucosa have a role in shaping or amplifying immune responses in RA joints.